Standardization Of Randang Eel Recipes In Nagari Tanjung Alam Batusangkar - Sarah Indah Naffira; Wiwik Gusnita (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
This study aims to standardize the eel randang recipe in Nagari Tanjung Alam Batusangkar which includes ingredients, spices, tools, processing methods and quality analysis in terms of shape, color, aroma, texture and taste. The background of the research was the differences in the use of basic spices, cooking techniques and the dosage in randang processing, resulting in inconsistent and varied quality. This type of research is a mixed method, which is a combination of qualitative and quantitative research. Qualitative data sources were obtained from people who were experts in making randang and quantitative data sources were obtained from 8 trained panelists who knew about randang. Based on the research results, the standard recipe for randang eel includes the main ingredients, spices, tools, processing techniques and quality. The organoleptic test of the standard eel randang recipe resulted in a fairly long shape quality, blackish brown color, quite fragrant aroma, oily dry enough textured bran, quite chewy and tender textured meat and pervasive flavor of spices and savory bran taste.